(untitled) (Dhaka University Law Journal, 2025)
Navigating the jurisprudence of the United Nations (UN) Human Rights Committee, the UN Committee on the Economic, Social, and Cultural Rights, and the European Court of Human Rights, this article shows that while the two committees are by and large committed to the idea of absolute inviolability of “essential core” of human rights, the Court shows an erratic commitment to the same. This article dubs commitment to absolute inviolability as essentialist and commitment to violability (i.e., “essential core” being violable under certain circumstances), as non-essentialist, and argues in favour of an essentialist approach.This article argues that commitment to essentialist approach can potentially help solve the prioritization/hierarchization dilemma, reduce the implementation gap between Civil and Political (CP) and Economic, Social and Cultural (ESC) rights, and in a way contribute to reconciling the universalist agenda of the International Human Rights Law (IHRL) with cultural relativism— each of these specifically speak to the feminist approaches to, and critiques of, the IHRL more generally and the intersectional feminist approaches to IHRL in particular. This motivates the author to call her standpoint in favouring the essentialist approach, an intersectional feminist one. Dhaka University Law Journal, 2024, 35 (1), 177-192